Sensitivity of urolithiasis detection using urinary, radiography and ultrasound parameters - De Lima, Charles Silva; Cintra, Cristiane Alves [UNESP]; Meirelles, Adriana Érica Wilkes Burton [UNESP]; Crivellenti, Sofia Borin; Mariani, Orlando Marcelo; Honsho, Daniel Kan; Santana, Aureo Evangelista [UNESP]; Carval, Marileda Bonafim [UNESP]; Canola, Julio Carlos [UNESP]; Crivellenti, Leandro Zuccolotto (Universidade Estadual de Londrina, 2017)
Although many information has been published regarding canine urolithiasis, sensitivity of radiography, ultrasound and urinary parameters have been poorly correlated with number, size, and composition of the stones. One hundred and thirteen clinical files of dogs with diagnosis of urolithiasis were retrospectively selected. Information regarding number, appearance, location, size, and composition of the stones were noted after surgical removed. Urolithiasis data was compared with radiographs and ultrasound images and urinalysis parameters. Pure struvite was found in 42.4% and calcium oxalate in 35.6%. Survey radiographs enabled the detection of radiopaque stones and when an ultrasound examination was also performed, the sensitivity was increased. Double contrast radiography enabled identification in 100% of radiolucent stones, and allowed for size measurement and number counts in 76.9% of radiolucent stones. Crystalluria had low sensitivity (31.5%) and specificity (58.8%). Hematuria (96.3%) and leukocyturia (61.1%) were the most common parameters found. We concluded that double contrast radiography can be considered the method of choice for detection of radiolucent stones. Crystalluria is not a good parameter to detect or predict type of stone. Hematuria and leukocyturia, although non-specific findings, can be used as triage for investigation of urolithiasis.
Keywords: Canine; Crystalluria; Stones; Urine